2009
DOI: 10.1080/15622970902960897
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anaesthetic medication on safety, tolerability and clinical effectiveness of electroconvulsive therapy

Abstract: Our study supports the hypothesis that inducting anaesthetic agents have a different impact on seizure duration, ictal and postictal electrophysiological indices and clinical efficacy of ECT. Compared to thiopental, which has been established as a standard anaesthetic during ECT, also the modern anaesthetic propofol is a suitable inducting agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…Also, Dew et al showed that shorter seizures were observed with thiopental sodium, which is not consistent with the present study [25]. But Eser and colleagues showed that Thiopental Sodium produced longer seizures than propofol, and also indicated that thiopental sodium and propofol were more effective than other anesthetic drugs in relation to their clinical effects in ECT [2], which is consistent with the results of this study. Regarding the controversial results, it seems that supplementary studies with the comparison of propofol, thiopental sodium and succinylcholine on the duration, quality and severity of seizure following ECT seem necessary.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Also, Dew et al showed that shorter seizures were observed with thiopental sodium, which is not consistent with the present study [25]. But Eser and colleagues showed that Thiopental Sodium produced longer seizures than propofol, and also indicated that thiopental sodium and propofol were more effective than other anesthetic drugs in relation to their clinical effects in ECT [2], which is consistent with the results of this study. Regarding the controversial results, it seems that supplementary studies with the comparison of propofol, thiopental sodium and succinylcholine on the duration, quality and severity of seizure following ECT seem necessary.…”
Section: Discussionsupporting
confidence: 58%
“…Electrotherapy or electroconvulsive therapy (ECT) is an effective strategy in the treatment of various types of psychiatric disorders [1,2]. ECT is one of the oldest treatments for mental illness [3] and is also a preferred method among all these modern treatments [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study aimed to demonstrate differences among these three agents. A retrospective study by Eser et al18 compared these anesthetics’ effects in ECT, but it included also patients anesthetized with methohexital. The authors concluded that thiopental and propofol are the most suitable induction agents during ECT.…”
Section: Discussionmentioning
confidence: 99%
“…Disadvantages include hypertension and occasional transient dissociative symptoms on wake up. 17 , 19 , 21 A recent systematic review concluded that robust evidence to recommend a particular induction agent for ECT is lacking and indicated that anesthetic agents should be chosen on the basis of adverse effect profile, emergence, and how these medications affect seizure duration. 18 Opioids, such as remifentanil and alfentanil, combined with anesthetic agents have been used to increase the seizure duration by an induction agent dose-sparing effect.…”
Section: Medications During the Ect Proceduresmentioning
confidence: 99%